WATER VOLUME TREATMENT FOR THE GROWTH OF OIL PALM SEEDLINGS (ELAEIS GUINEENSIS JACQ) FROM TWIN MAIN NURSERIES IN ULTISOL SOIL - Hidayatullah Hidayatullah; Ida Nursanti; Hayata Hayata (International Research of Multidisciplinary Analysis, 2023)
Oil palm seeds that come from twin sprouts are very sensitive to the need for water, if it is too late to provide water, the plant seeds will respond immediately resulting in the plant seeds withering, drying out over time and eventually dying. This study aims to determine the effect of giving water with different volumes on the growth of oil palm seedlings from twins in ultisol soil. This study used a completely randomized design (CRD) and the treatment design was rice husk charcoal with 4 treatment levels including; P1: Giving 500 ml of water, P2: Giving 400 ml of water, P3 Giving 300 ml of water, P4: Giving 200 ml of water. Data were analyzed using analysis of variance, followed by Duncan's Multiple Range Test (DNMRT) at Î± level of 5%. The results showed that the volume of water given at doses of 500 ml, 400 ml, 300 ml and 200 ml had no significant effect on plant height, fresh weight and root dry weight of twins of oil palm (Elaeis guineensis Jacq) seedlings. The P3 treatment with a volume of 300 ml of water showed a high yield of 65.33 cm oil palm plants, which exceeded the normal growth standards for oil palm seedlings